2015
DOI: 10.1097/md.0000000000000520
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Companions of Stroke Patients

Abstract: Acute care of stroke victims largely relies on the rapid identification and timely clinical and radiological assessment. We evaluated the effect of the number of patient companions on the efficiency of the diagnostic process in the emergency department (ED).Consecutive stroke patients admitted to the ED between August 2011 and October 2012 were evaluated. Clinical, epidemiological, and timeline data (symptoms onset, ED arrival, computed tomography [CT] scanning, and recombinant tissue plasminogen activator inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…This corresponds with our findings on the perceived seriousness of the situation in patients and bystanders. In line with our study, some studies have found that bystander presence increases the use of EMS, 2729 and others have also found an association to reduced prehospital delay. 7,10,29 However, the role of the bystander and the patient’s type of social network may play an important role, as smaller social networks (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…This corresponds with our findings on the perceived seriousness of the situation in patients and bystanders. In line with our study, some studies have found that bystander presence increases the use of EMS, 2729 and others have also found an association to reduced prehospital delay. 7,10,29 However, the role of the bystander and the patient’s type of social network may play an important role, as smaller social networks (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…Subsequent iterations of the MSU have adapted to their respective settings. Larger vehicles have the advantage of carrying larger scanners and more specialized personnel, robustness in rural off-road conditions, and allowing relatives to accompany patients to provide history and procedural consent (79). Smaller vehicles may have greater access to narrow roads and lower cost.…”
Section: Adapting Msu Approaches To Rural Healthcarementioning
confidence: 99%
“…In the case of stroke, patients with a companion during a medical visit are about 1.7 times more likely to have than older adults without stroke (Price et al, 2019). Research from Ashkenazi et al suggests that family members and other companions could facilitate faster and more effective emergency department (ED) management of stroke patients, possibly improving their outcomes (Ashkenazi et al, 2015). Besides, information from companions can be used to assess the quality of life when patients are incapable of reporting their condition (Medea et al, 2021).…”
Section: Introductionmentioning
confidence: 99%